Correction: Dye adsorption mechanisms in TiO2 films, and their effects on the photodynamic and photovoltaic properties in dye-sensitized solar cells. Issue 7 (21st January 2016) - Hwang, Kyung-Jun; Shim, Wang-Geun; Kim, Dajung; An, Jongdeok; Im, Chan; Kim, Youngjin; Kim, Gunwoo; Choi, Chulmin; Kang, Sang Ook; Cho, Dae Won
Abstract : Correction for 'Dye adsorption mechanisms in TiO2 films, and their effects on the photodynamic and photovoltaic properties in dye-sensitized solar cells' by Kyung-Jun Hwang et al., Phys. Chem. Chem. Phys., 2015, 17, 21974–21981.